ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Studi Empiris Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia) - Sholihin, Muhammad Rijalus; Harnovinsah, Harnovinsah (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2017)
Issues raised in this research is how the influence of institutional ownership variable, independe board of directors, audit committee, and the size of the company to the level of disclosure in the company's Corporate Social Responsibility manufactur in Indonesia Stock Exchange. This study aimed to analyze the influence of these variables, and to contribute in the form of useful information for investors, owners, and company management in decision making. Variable selection based on the relevant theory and reference the results of previous research related to the study. The research methodology uses quantitative methods, the amount of a total of 106 observations sourced from 53 companies during the second annual period. The results of this study found that the variables of institutional ownership, board of commissioners independe, audit committee, and the size of the company turns its influence signifkan on the level of disclosure of Corporate Social Responsibility when viewed simultaneously, but when viewed in partial only institutional ownership and the size of the companies that have significant influence, while the other two did not have a significant influence